Infrastructure Nationalism and Political Vulnerability – Examining the Stalled Negotiations Over the Bagamoyo Port Project During Magufuli's Reign. (May 2023) - Barton, Benjamin
The Bagamoyo Port Project (BPP) was meant to have set in motion the development of East Africa's largest port. Yet, with the advent of former President John P. Magufuli to power in October 2015, the BPP has led a chequered existence. This article explores the dynamics behind the stalled talks over the BPP by emphasising Magufuli's penchant for developmentalism, nationalism and authoritarianism ultimately as a political strategy designed to mask his vulnerable electoral standing within the party and with the electorate. The renegotiations over the BPP served as an ideal opportunity in this regard to shore up his base.